Clinical characteristics and outcomes of colorectal cancer in the ColoCare Study: differences by age of onset - Himbert, Caroline; Figueiredo, Jane C.; Shibata, David; Ose, Jennifer; Lin, Tengda; Huang, Lyen C.; Peoples, Anita R.; Scaife, Courtney L.; Pickron, Bartley; Lambert, Laura; Cohan, Jessica N.; Bronner, Mary; et al. (Cancers, 2021)
Early-onset colorectal cancer has been on the rise in Western populations. Here, we compare patient characteristics between those with early- (<50 years) vs. late-onset (≥50 years) disease in a large multinational cohort of colorectal cancer patients (n = 2193). We calculated descriptive statistics and assessed associations of clinicodemographic factors with age of onset using mutually-adjusted logistic regression models. Patients were on average 60 years old, with BMI of 29 kg/m2, 52% colon cancers, 21% early-onset, and presented with stage II or III (60%) disease. Early-onset patients presented with more advanced disease (stages III-IV: 63% vs. 51%, respectively), and received more neo and adjuvant treatment compared to late-onset patients, after controlling for stage (odds ratio (OR) (95% confidence interval (CI)) = 2.30 (1.82-3.83) and 2.00 (1.43-2.81), respectively). Early-onset rectal cancer patients across all stages more commonly received neoadjuvant treatment, even when not indicated as the standard of care, e.g., during stage I disease. The odds of early-onset disease were higher among never smokers and lower among overweight patients (1.55 (1.21-1.98) and 0.56 (0.41-0.76), respectively). Patients with early-onset colorectal cancer were more likely to be diagnosed with advanced stage disease, to have received systemic treatments regardless of stage at diagnosis, and were less likely to be ever smokers or overweight.